Electrical and dielectric properties of solid and nanocomposite polymer electrolytes based on chitosan / Shujahadeen Bakr Aziz - Bakr Aziz, Shujahadeen (2012)
In solid polymer electrolytes (SPEs) and nano-composite polymer electrolytes (NCPEs) the ion conduction mechanism is still not well understood. This motivates us to study the electrical and dielectric properties of solid polymer electrolytes (CS:AgTf, CS:LiTf and CS:NaTf ) and nano-composite polymer electrolytes ((1-x)(0.9CS:0.1AgTf)-xAl2O3 (0.02 ≤ x ≤ 0.1), (1-x)(0.9CS:0.1NaTf)-xAl2O3 (0.02 ≤ x ≤ 0.1) and (1- x)(0.9CS:0.1LiTf)-xAl2O3 (0.02 ≤ x ≤ 0.1)) based on chitosan. In the present work the SPEs and NCPEs were prepared by the solution cast technique. The XRD results reveal the increase of amorphous fraction in chitosan upon the addition of salts. The UV-vis, TEM, SEM and EDX analysis confirms the formation of metallic silver nanoparticle in CS:AgTf system. The dependence of DC conductivity and dielectric constant on salt concentration is almost the same. In CS:AgTf, CS:NaTf and CS:LiTf systems the DC conductivity follows the Arrhenius equation. The DC conductivity and dielectric constant for these SPEs have been correlated at different temperatures. The preexponential factor is independent on dielectric constant and temperature for these SPEs. The broadness of loss tangent peaks and incomplete semicircles of Argand plots reveals the non-Debye relaxation. The impedance plots and AC conductivity spectra at different temperatures were used to confirm the effect of electrode polarization on AC conductivity dispersion. The calculated frequency exponent (s) at different temperatures was used to characterize ion conduction model for each system. To produce NCPEs the Al2O3 nanoparticle (size < 50 nm) were added to SPEs (CSA6, CSB6 and CSC6). The XRD results revealed the increase of amorphous regions (small crystallite size) in NCPEs up to 4 wt.% of Al2O3. At high alumina concentration the crystallinity of these NCPEs are increased. The SEM analysis shows a well dispersed Al2O3 nanoparticle at low concentration and a cluster formation at high alumina concentrations. The EDX analysis reveals that the white clusters are mostly alumina nanoparticles. The DC conductivity and bulk dielectric enhancement of these NCPEs reveal the role played by alumina nanoparticles. The curvature of DC conductivity versus 1000/T at higher temperatures were observed for these NCPEs. The drop in DC conductivity at a particular temperature for these three NCPEs can be ascribed to the phase transition of alumina ceramic from ferroelectric to paraelectric. The DC conductivity and dielectric constant study performed at different temperatures are well correlated for these NCPEs. However, the pre-exponential factor and dielectric constant cannot be correlated. The pattern of Arrhenius and compensated Arrhenius are almost the same. The broad loss tangent peaks and electric modulus (Argand plots) reveal the distribution of relaxation times. The electrode polarization effect was clearly observed in the study of impedance plots and AC conductivity spectra at different temperatures. The temperature dependences of frequency exponent were used to specify the ion conduction model for each NCPE system.